Acute aortic dissection during pregnancy: Trials and tribulations. Issue 5 (29th September 2020) - Rimmer, Lara; Heyward‐Chaplin, Jessica; South, Matthew; Gouda, Mohamed; Bashir, Mohamad
Abstract: Background: Type A acute aortic dissection (TAAD) during pregnancy is a life‐threatening event for both the mother and the unborn baby. Pregnancy has been recognized as an independent risk factor for TAAD, postulated to be due to physiological changes that cause hyperdynamic circulation. This review seeks to outline the current controversies around this unique group. Methods: A comprehensive literature search was carried out across large databases to assimilate relevant papers regarding acute aortic dissection in pregnant women. Results: The presentation can be atypical in many cases and further concern from clinicians of fetal radiation exposure can result in missed or delayed diagnoses. Investigation via the quickest form of imaging, whether computed tomography, magnetic resonance imaging, or transesophageal echocardiography, should be carried out promptly due to the high risk of mortality. Surgical management of TAAD in pregnancy revolves primarily around the decision to deliver the fetus concomitantly or to perform the aortic repair with the fetus in utero. Conclusions: Management of this group includes rapid and dynamic assessment without delay. From conception to postpartum, there are multiple stages in which to manage these women. Challenges in carrying out management in the form of operative techniques and cardiopulmonary bypass place the fetus at risk and must be approached with caution, particularly as there is little evidence‐base for many of these decisions. Further research into reducing maternal and fetal mortality is necessary.